(untitled) (Cadernos de Ética e Filosofia Política, 2015)
The text approach the relation doxa and truth in the theory of Hannah Arendt action, with the intention to evidence a tension between stability and instability in the action topic. It is also shown how the attempt to control the instability, made by the political philosophy, meant an excess of philosophize in the field of human affairs.